2020
DOI: 10.1038/s41598-020-72046-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of collagen matrix on postoperative palatal fistula in cleft palate repair

Abstract: Palatal fistula is a challenging complication following cleft palate repair. We investigated the usefulness of collagen matrix in the prevention of postoperative fistula. We performed a retrospective cohort study of patients with cleft palate who underwent primary palatoplasty (Furlow’s double opposing z-plasty) in Seoul National University Children’s Hospital. Collagen Graft and Collagen Membrane (Genoss, Suwon, Republic of Korea) were selectively used in patients who failed complete two-layer closure. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…experience-based outcome study revealed a rate of velopharyngeal insufficiency as low as 5.5 percent. 15 Future well-designed studies could also draw conclusive answers regarding the prophylactic purpose of split buccal fat flaps compared with other approaches using autogenous tissues or synthetic biomaterials, such as buccal myomucosal flap, autologous platelet-rich plasma, hemostatic gelatin sponge, collagen membrane, and acellular dermal matrix 5,[21][22][23] for prevention of postoperative palatal fistula and scar contraction.…”
Section: Discussionmentioning
confidence: 99%
“…experience-based outcome study revealed a rate of velopharyngeal insufficiency as low as 5.5 percent. 15 Future well-designed studies could also draw conclusive answers regarding the prophylactic purpose of split buccal fat flaps compared with other approaches using autogenous tissues or synthetic biomaterials, such as buccal myomucosal flap, autologous platelet-rich plasma, hemostatic gelatin sponge, collagen membrane, and acellular dermal matrix 5,[21][22][23] for prevention of postoperative palatal fistula and scar contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Palatal fistula is a challenging complication following cleft palate repair [ 2 - 4 ]. Reparative surgery is complex because of inevitable scarring, altered vascularity, and persistent tension after primary palatoplasty [ 5 - 7 ]. However, watertight, tension-free closure of the palate fistula remains the primary treatment of choice, especially for wide fistulas [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of postoperative fistula formation varies depending on the surgical technique used, however typically falls around 2.4 to 35%. 20 Repair under tension is the main trigger of oronasal fistula (ONF) development, and the accessible tissue to repair the palate appears to be insufficient. The risk of developing the ONF is higher in these instances, but it could be avoided in the hands of a skilled practitioner.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported absence of fistula development after cleft palate repair that supports our results. 19,20 This could be linked to the exclusion of patients with very wide palatal clefts and smaller number of the study group. Some studies reported that fistula rate was higher for the more sever degree of clefting.…”
Section: Discussionmentioning
confidence: 99%